Price stabilization and the management of public foodgrain stocks in Bangladesh - Goletti, Francesco (International Food Policy Research Institute, 2000)
This chapter reviews the case for price stabilization and the continued maintenance of large public foodgrain stocks in Bangladesh. It begins with an assessment of the relative importance of private markets and public interventions as forces in declining price volatility. Discussion then turns to rationales for continued price stabilization, which center around new, lower levels of price variation. Finally, the chapter evaluates the level of public stocks required to meet two main objectives: price stabilization and emergency response to natural disasters.